2022
DOI: 10.1055/s-0042-1745771
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Proximal Contact Loss between Implant-Supported Prostheses and Adjacent Natural Teeth: An Umbrella Review

Abstract: Contact loss between the implant prosthesis and adjacent natural teeth is a clinical complication whose overall prevalence is uncertain. Therefore, the main purpose of this umbrella study was to evaluate the extent of contact loss between implant prostheses and adjacent natural teeth. Electronic database of MEDLINE/PubMed, Cochrane, and Google Scholar was searched until August 2021 without considering language restrictions and according to Preferred Report Items for Systematic and Meta-Analysis guidelines (pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“… 8 , 10 Interesting knowing that interproximal contact loss was about three times more prone to occur in the mesial side of the restorations than in the distal after the implant-supported single crowns (SCs) had been delivered over 11 years and was known to be associated with food impaction. 1 , 4 , 10 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 10 Interesting knowing that interproximal contact loss was about three times more prone to occur in the mesial side of the restorations than in the distal after the implant-supported single crowns (SCs) had been delivered over 11 years and was known to be associated with food impaction. 1 , 4 , 10 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…The interproximal contact plays an important role to protect the periodontal and peri-implant tissue against the damage caused by food impaction. 13 , 15 , 16 Interproximal contact loss may lead to food impaction, and results in subsequently complications such as periodontal defects, 13 , 17 , 18 recurrent decay, 19 and peri-implant tissue complications. 2 , 19 , 20 In terms of periodontal tissue, some studies reported that interproximal open contacts were related to clinical attachment loss, deeper probing depths, and processing bone loss.…”
Section: Introductionmentioning
confidence: 99%